mSphere of Influence: Resolution of the Structure of an Influenza Virus Polymerase Is a Game Changer - Mathilde Richard (American Society for Microbiology, 2019)
ABSTRACT Mathilde Richard works in the field of virology, more specifically on the evolution and pathogenesis of influenza viruses. In this mSphere of Influence article, she reflects on how the two articles “Structure of Influenza A Polymerase Bound to the Viral RNA Promoter” by A. Pflug, D. Guilligay, S. Reich, and S. Cusack (Nature 516:355–360, 2014, https://doi.org/10.1038/nature14008) and “Structural Insight into Cap-Snatching and RNA Synthesis by Influenza Polymerase” by S. Reich, D. Guilligay, A. Pflug, H. Malet, I. Berger, et al. (Nature 516:361–366, 2014, https://doi.org/10.1038/nature14009) made an impact on her by providing new grounds to study the influenza virus polymerase and its role in virus biology and evolution.